Pendidikan Multikultural Dalam Menumbuhkan Perilaku Prososial Siswa Pada Masyarakat Heterogen - Hakim, Firdha Ainil; F, Firman; N, Nurfarhanah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Multicultural education has a strategic role in shaping students’ prosocial behavior in a diverse society. Behaviors such as sharing, helping, and cooperation grow through an understanding of cultural, ethnic, and religious diversity. This research highlights how multicultural values integrated in curriculum and learning are able to increase students’ empathy, solidarity, and social awareness with the literature study method. Schools with high diversity show that an inclusive learning environment reduces identity conflicts and encourages positive interactions. Key success factors include teacher competence, supportive of an open school environment, and student participation in cross-cultural activities. Multicultural education not only shapes the prosocial character of students, but also strengthens social cohesion in a peaceful and tolerant pluralistic society.